A Systematic Review On The Assessment Of Infection In The Elderly With Covid-19 And Fractures In ICU Based On Analgesia Point (Journal of Pharmaceutical Negative Results, 2023)
This study has examined the principles of care of the medical staff for the elderly with fracture problems and corona virus in the special care unit. While the Chinese health authorities had previously reported the average age of the disease to be 75 years. Elderly people, especially people with lung problems, have a mortality rate of about 15%. The coronavirus acts like a seasonal flu. According to the US Centers for Disease Control and Prevention (CDC), between 70 and 85 percent of all flu-related deaths and 50 to 70 percent of flu-related hospitalizations are among people over the age of 65. The most at-risk group is the elderly who live in day care centers. Among recovered patients with coronavirus in China, there is evidence that some of these patients have long-term lung damage. The researchers announced that among the 70 recovered patients, lung damage was observed in 66 of them in the CT scan. These injuries are caused by a build-up of hardened tissue that blocks blood vessels in tiny air sacs called alveoli, said Yuhei Wang, a radiologist at Huazhong University of Science and Technology in Wuhan, China. Alveoli absorb oxygen to form tissue debris around them. Tissue lesions can be a chronic symptom of lung diseases, including SARS and MERS, similar injuries were observed in recovered patients.